KARAKTERISTIK PEMERINTAH, TEMUAN AUDIT DAN KINERJA KEUANGAN PEMERINTAH PROVINSI BENGKULU - Afriansyah, Berli; Fadli, Fadli; Usman, Darman (UNIB Press, 2017)
This study aims to examine the effect of measures of government characteristics and audit findings on the financial performance of the district/city government of Bengkulu Province. The government characteristics observed consist of the size of government, regional wealth, dependence on central funds, administrative age, and balance funds.The subjects in this study were regencies/cities in Bengkulu Province which consisted of 9 regencies and one city. The data collection technique in this research is document analysis, namely secondary data in the form of local government financial reports for 2011-2015. The data analysis technique used a multiple linear regression test.The results showed that: government size, regional wealth, dependence on central funds, administrative age, balanced funds, and audit findings had no effect on financial performance in the Municipal / Regency government of Bengkulu Province